INTEGRATING SOCIAL EMOTIONAL LEARNING INTO ISLAMIC EDUCATION FOR AKHLAK FORMATION IN THE SOCIETY 5.0 ERA : - Salwa Rihadatul Aisy; Syahidin; Agus Fakhruddin (Referensi Islamika: Jurnal Studi Islam, 2026)
This study explores how Social Emotional Learning (SEL) is integrated into Islamic Education to support akhlak formation among elementary school students in the Society 5.0 era. It also examines how SEL competencies are reflected in Islamic Education practices and how they appear to support students' socio-emotional and moral development. This study employed a qualitative descriptive design within a constructivist paradigm. Data were collected through semi-structured interviews with three Islamic Education teachers and three fourth-grade students, as well as document analysis of teachers' lesson plans (RPP), at SD Yasporbi III. Participants were selected using purposive sampling. The data were analyzed using thematic analysis through coding, categorization, interpretation, and triangulation. The findings indicate that SEL-related practices were integrated into Islamic Education through religious habituation, reflective activities, emotional guidance, dialogue, restorative approaches, and collaborative learning. These practices appeared to support the development of socio-emotional competencies, including emotional regulation, empathy, self-awareness, and responsible decision-making, which participants perceived to be associated with students' akhlak development. The findings also suggest that the Society 5.0 era presents challenges to akhlak formation through increased digital media exposure, online interactions, and technological distractions, highlighting the importance of strengthening students' self-regulation and digital responsibility. Furthermore, the study identified initial conceptual components of an SEL-integrated Islamic Education framework that combines cognitive, spiritual, emotional, and social dimensions of learning. This study contributes to the discourse on integrative Islamic Education by demonstrating how selected SEL competencies can be contextualized within Islamic moral and spiritual values, particularly through practices that foster self-awareness (muhasabah), self-regulation (sabr), empathy (rahmah), and responsible decision-making (amanah). Unlike previous studies that have primarily examined SEL from secular educational perspectives or discussed Islamic moral education separately, this study offers a contextual perspective on integrating SEL with Islamic values to support akhlak formation in elementary Islamic Education. Rather than proposing a validated instructional model, the study identifies initial conceptual components that may inform future research on SEL-integrated Islamic Education in the Society 5.0 era.